ANALISIS DAMPAK PEMEKARAN DAERAH DITINJAU DARI ASPEK PERCEPATAN PERTUMBUHAN EKONOMI DAN PENINGKATAN KUALITAS PELAYANAN PUBLIK (Studi Pemekaran Kabupaten Kepulauan Meranti dari Kabupaten Bengkalis) - Abdul Hakim; Wahyu Hamidi; Dahlan Tampubolon (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Since the enectment of Law No. 22 year 1999 on Regional Government, the phenomenon of regional expansion in indonesia was growing. Post-birth of the Act, in Riau province have formed a new autonomous region 6 under Law No. 53 Year 1999. From 6 DOB formed, Kepulauan Meranti Regency is DOB youngest of which was formed in 2009 under Law No.12 Year 2009. This study to analyze the impact of Regional Expansion Kepulauan Meranti regency after the secession of the District Bangkalis especially from the aspect of accelerating economic growth and improving the quality of public services. This research uses descriptive quantitative methode and test hypotheses using t-test.The results of this study showed that there was no significant difference on the performance of the regional economy Kepulauan Meranti regency after the expansion, the impact of the expansion have not indicated a positive result of the acceleration of economic growth while the performance of public services there are significant differences after the expansion, the impact of the division showed positive results towards improving the quality of local public services. This is thought to occur because the area is getting smaller so that the span of control is getting better.Keyword: Regional Expansion, New Autonomous Regional, The Regional Economic, Public Service.